Repurposing of substances with lactone moiety for the treatment of γ-Hydroxybutyric acid and γ-Butyrolactone intoxication through modulating paraoxonase and PPARγ - Fateh, Sepand Tehrani; Salehi-Najafabadi, Amir (Frontiers in Pharmacology, 2022)
GHB and GBL are highly accessible recreational drugs of abuse with a high risk of adverse effects and mortality while no specific antidotes exist. These components can also be found in the clinical setting, beverages, and cosmetic products, leading to unwanted exposures and further intoxications. As the structural analogue of GABA, GHB is suggested as the primary mediator of GHB/GBL effects. We further suggest that GBL might be as critical as GHB in this process, acting through PPARγ as its receptor. Moreover, PPARγ and PON (i.e., the GHB-GBL converting enzyme) can be targeted for GHB/GBL addiction and intoxication, leading to modulation of the GHB-GBL balance and blockage of their effects. We suggest that repurposing of substances with lactone moiety such as bacterial lactones, sesquiterpene lactones, and statins might lead to potential therapeutic options as they occupy the active sites of PPARγ and PON and interfere with the GHB-GBL balance. In conclusion, this hypothesis improves the GHB/GBL mechanism of action, suggests potential therapeutic options, and highlights the necessity of classifying GBL as a controlled substance.